2011
DOI: 10.1038/ijo.2011.129
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of A1 and A2b adenosine receptors on adipogenesis

Abstract: Background: Adenosine mediates its actions through four G protein-coupled receptors, A1, A2a, A2b and A3. The A1 receptor (A1R) is dominant in adipocytes where it mediates many actions that include inhibition of lipolysis, stimulation of leptin secretion and protection against obesity-related insulin resistance. Objective: The objective of this study is to investigate whether induced expression of A1Rs stimulates adipogenesis, or whether A1R expression is a consequence of cells having an adipocyte phenotype. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 29 publications
3
65
1
Order By: Relevance
“…However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40]. We did observe small stimulatory effects of 2-chloroadenosine on rat bone marrow osteoblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results are at variance with several studies which found that adenosine or adenosine analogues, acting via the A 2A or A 2B receptors, stimulate the differentiation and function of human and rodent bone marrow osteoblasts and promote bone regeneration [24,30,31,40]. Our data also do not concur with the reported inhibitory effects of adenosine analogues, acting via A 1 or A 2A receptors, on the differentiation of rodent osteoblast-like cells [41] or human osteoblasts [40]. We did observe small stimulatory effects of 2-chloroadenosine on rat bone marrow osteoblasts.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the effects described by Teramachi and colleagues are most likely mediated by A 2b receptors on osteoblasts since, as noted in their work, the primary reason for inhibition of osteoclast formation in these bone marrow cultures was inhibition of RANKL expression without diminution of osteoprotegerin expression. Since RANKL, the principal stimulus for osteoclast differentiation, is primarily expressed on osteoblasts, which have been previously shown to express A 2b receptors which affect their function [50][51][52], the most likely explanation for the observed effects of A 2b receptor ligation on osteoclastogenesis is inhibition of osteoblast-mediated stimulation of osteoclastogenesis. It is also interesting to note that it is likely that the inhibitory effects of methotrexate on osteoclast-mediated bone destruction are mediated by the higher levels of adenosine released by methotrexate-treated cells and tissues which interact with A 2A and A 3 receptors [53].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Gharibi et al (35) reported that, although A1R was expressed in osteoblast precursors, it was involved in induction of adipocyte differentiation rather than osteoblast differentiation. Nonetheless, Katebi et al (36) reported that adenosine, acting via A2AR, plays a critical role in promoting the proliferation of mouse bone marrowderived fibroblast-like mesenchymal stem cells, and Gharibi et al (22) reported that A2AR is up-regulated in later osteoblast differentiation stages, but stimulation of A2AR more strongly promotes adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%